(Invited) Simulation and Modeling of the Switching Dynamics in Resistive Switching Devices. (9th September 2015) - Menzel, Stephan
Abstract : Resistive switching devices based on the electrochemical mechanism (ECM) or the valence change mechanism (VCM) have attracted great attention due to their potential use in future non-volatile memories. The paper presents physics-based simulation models for ECM and VCM cells that can reproduce the key switching phenomena: I-V characteristics, highly nonlinear switching kinetics and multilevel switching. The physical processes that lead to the nonlinear switching kinetics will be discussed in detail.